2009
DOI: 10.1002/eqe.977
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tests of four two‐story narrow steel plate shear walls—Part 1: Analytical studies and specimen design

Abstract: SUMMARYThis study consists of two parts. In this two-part research, four two-story narrow steel plate shear walls (SPSWs) were cyclically tested at the Taiwan National Center for Research on Earthquake Engineering in 2007. This paper, Part 1, proposes a capacity design method for the first-story boundary column of the SPSW to ensure that the plastic hinges form at the column bottom ends when the SPSW develops the plastic mechanism. The design method was developed based on the superposition method considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…These specimens possessed satisfactory ductility and load-carrying capacity, making it evident that strong 1F column specimens develop the uniform yielding mechanism suggested by [9]. In the present study, considering the combined effects of the frame sway action and the panel forces, a capacity design method ensuring the plastic hinge formation at the 1F columns' bottom ends has been developed and presented in Part 1 [10].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…These specimens possessed satisfactory ductility and load-carrying capacity, making it evident that strong 1F column specimens develop the uniform yielding mechanism suggested by [9]. In the present study, considering the combined effects of the frame sway action and the panel forces, a capacity design method ensuring the plastic hinge formation at the 1F columns' bottom ends has been developed and presented in Part 1 [10].…”
Section: Introductionmentioning
confidence: 86%
“…This paper presents the cyclic test results of four full-scale two-story narrow SPSWs conducted at NCREE in 2007 [10]. The key objectives of the experiments include: (1) verify the effectiveness of the proposed column capacity design; (2) investigate the effects of the proposed restrainers in reducing the force demands on the boundary elements; (3) investigate the cyclic performance of the narrow SPSWs with a panel width-to-height aspect ratio of about 0.6.…”
Section: Introductionmentioning
confidence: 99%
“…The passive method reduces tension field forces acting on the column by restraining the infill steel plate and delaying buckling and formation of the tension field. This has been done either by using a concrete wall attached to the steel infill plate by shear studs or bolts (Zhao and Astaneh-Asl, 2004), or by adding steel restrainers to the infill plate to delay its buckling until the infill plate yields in shear Tsai et al, 2010;Nie et al, 2012). Weakening of the infill plate have also been tried by creating a regular pattern of circular perforations (Roberts and Sabouri-Ghomi, 1992;Vian et al, 2009), or by using low yield point (LYP) steel plates (Vian et al, 2003).…”
Section: Background and The Past Researchmentioning
confidence: 99%
“…They concluded that column flexibility parameters can significantly affect the behavior of SPSWs. Some studies such as Tsai and Li [9] and Alavi and Nateghi [10], further investigated SPSWs with various types of stiffeners including longitudinal stiffener, transverse stiffener, cross stiffener, diagonal stiffener, vertical and horizontal ribbed stiffener, etc. Sabouri-Ghomi and Mamazizi [11] tested two one-story SPSWs with and without stiffeners and one of their surrounding frames, and then studied their behavior.…”
Section: Introductionmentioning
confidence: 99%